Parents’ Attitude to the Double Reduction Policy and Its Influencing Factors from the Perspective of ABC Model - Yuting Wang; Guanqiao Wang; Hui Zhang (Journal of Advanced Research in Education, 2022)
Parental attitude is one of the important factors to promote the formation of the long-term mechanism of the double reduction policy (DRP). By exerting ABC Model, the questionnaire and interview are designed to investigate the attitudes and influencing factors from the parents of middle school students in Nanchong towards the DRP from the three dimensions. Three dimensions are cognition, behavior, and affect. Parental attitudes studied contributes to the formation of long-term mechanism of the DRP. The results show that on the affect dimension, the parental attitude of supporting the DRP policy has a significant positive impact; parental cognition of the DRP shows positive impact on students’ learning and school education; in behavioral indicators, parental attitude towards the DRP confirms positive supportive behavior. Three suggestions are proposed based on the findings.